2013
DOI: 10.1530/rep-13-0267
|View full text |Cite
|
Sign up to set email alerts
|

Role of selenium and glutathione peroxidase on development, growth, and oxidative balance in rat offspring

Abstract: Selenium (Se), an essential trace metal, is important in both growth and reproduction and is the constituent of different selenoproteins. The glutathione peroxidase (GPx) family is the most studied as it prevents oxidative stress. Liver oxidation is considered as another mechanism involved in low birth weight. Therefore, in order to ascertain whether GPx is related to the effects of Se on growth during gestation and lactation, three groups of rat pups were used: control, Se deficient (SD), and Se supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…Chemical compounds that contain SH, such as selenium, alpha lipoic acid, and N-acetyl cysteine, may be used in new studies that concern SAR therapy. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Chemical compounds that contain SH, such as selenium, alpha lipoic acid, and N-acetyl cysteine, may be used in new studies that concern SAR therapy. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Se also plays a role in reproduction, where it is essential for sperm production. In goats, maternal supplementation with Se during gestation and lactation influences the oxidative status and expression of apoptotic genes in the testes of offspring [ 17 ] while a recent rat study demonstrated that low Se levels were also associated with changes in intrauterine growth and liver metabolism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on liver and colon because earlier work has shown that low Se affects liver metabolism in utero [ 18 , 25 ], and Se levels have also been reported to affect both intestinal growth in the early life of the lamb, and to influence susceptibility to colorectal cancer in the adult human [ 12 , 28 , 29 ]. The liver is an important Se reservoir and dietary Se and folate treatment together have an important effect on liver function resulting in increased Se deposits and balanced Se bioavailability [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct and indirect relationships between selenium and 40 common diseases have been reported (Nogales et al 2013;Hatfield et al 2012) may affect plant nitrogen metabolism and nutritional ingredients (Zhang et al 2012a;Taiwo and Oso 1997;Macedo et al2013;Masakapalli et al2013). Carbendazim treatment, therefore, may have a significant impact on the nutritional value of a crop and on the medicinal value of medicinal plants, resulting in unpredictable effects on the human body.…”
Section: Discussionmentioning
confidence: 99%